1993
DOI: 10.1073/pnas.90.17.8108
|View full text |Cite
|
Sign up to set email alerts
|

Production of unmodified human adult hemoglobin in Escherichia coli.

Abstract: We have constructed a plasmid (pHE2) in which the synthetic human a-and 3-globin genes and the methionine aminopeptidase (Met-AP) gene from Escherichia coli are coexpressed under the control of separate tac promoters. The Hbs were expressed in E. coli JM109 and purified by fast protein liquid chromatography, producing two major components, a and b. Electrospray mass spectrometry shows that at least 98% and about 90% of the expressed a and (3 chains of component a, respectively, have the expected masses.The rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
235
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(241 citation statements)
references
References 36 publications
4
235
2
Order By: Relevance
“…Cells were grown in DM-4 medium (25) at 30°C in a 20-liter fermenter (B. Braun Biotech International, model Biostat C). The induction and purification of rHb were carried out as described previously (26). Hb A and Hb S from whole blood were purified according to established methods in our laboratory (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown in DM-4 medium (25) at 30°C in a 20-liter fermenter (B. Braun Biotech International, model Biostat C). The induction and purification of rHb were carried out as described previously (26). Hb A and Hb S from whole blood were purified according to established methods in our laboratory (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids were transfected into E. coli (JM 109) (Promega Co.), bacteria were grown at 30°C, and soluble ␤-globin chain variants were isolated as described (5,8). Expression and purification of ␤-globin variants were basically as described previously (5,8). However, cationexchange chromatography on a Source 15 S column (Amersham Pharmacia Biotech) instead of Superose 12 gel filtration was used for purification of the ␤ chain variants.…”
Section: Expression Of Soluble Recombinant Human ␤-Globin Chain Variantsmentioning
confidence: 99%
“…␤112 Ser, ␤112 Val, ␤112 Thr, and ␤112 Asp) were constructed and expressed using the pHE2␤ plasmid vector that contains cDNAs coding for each ␤ chain variant and methionine aminopeptidase which was originally developed to express ␣ and ␤ chains at the same time (8,9). The basic strategy for generation of these variants by site-specific mutagenesis of the normal ␤ chain involves recombination/polymerase chain reaction as described previously (10).…”
Section: Expression Of Soluble Recombinant Human ␤-Globin Chain Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the assembly of myosin heavy and light chains occurs in E. coli, but the protein has not been fully characterized (McNally et al, 1988). The two subunits of hemoglobin have been coexpressed in E. coli and shown to renature into a functional tetrameric complex (Hoffman et al, 1990;Shen et al, 1993). The overexpression of the chaperones in E. coli cells expressing human procollagenase results in an increase in the accumulation and solubility of this protein in the cytoplasm, but it is not clear if the resulting protein is functional (Lee and Olins, 1992).…”
mentioning
confidence: 99%